Traditional Communication and Language Power In The Deliberative Culture Of “Lonto Leok” - Manafe, Yermia Djefri; Hadi, Ido Prijana; Jama, Karolus Budiman (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
Communication of traditional elite power relations and language power over silent groups in the "Lonto Leok" deliberation culture greatly influences the results of deliberations which essentially ignore the opinions of the lower community, so that the democracy that occurs seems to represent all community opinions. Therefore, it is necessary to know the power relations of traditional elites with the community (silent groups) in order to gain an understanding of this democratic context. This research was conducted among the Manggarai ethnic group in Manggarai Regency, East Nusa Tenggara Province using qualitative methods. Data collection was conducted by in-depth interviews with local elites and people who practice the "lonto leok" culture. To get the appropriate views, focused discussions were conducted to match the results of the interviews. The results of this study concluded that the lonto leok culture is a form of deliberation in the context of the Manggarai indigenous community, where the customary elite (traditional elite) has a very strong role in decision-making which is implicitly supported by the power of language to silence the lower layers of society (non-elite) to prevent dissent.